A Role of Keywords in the Network Searching Era - HIRAWA, Mariko (Igaku Toshokan, 1998)
Today, a number of libraries has increased who can open their Online Public Access Catalog (OPAC) to the public on the Internet. An investigation was conducted, through World Wide Web OPACs, regarding the setting of conditions of search fields, varied fields for keywords access, and appropriate methods for creating keywords. The findings suggest that present OPACs are not capable of storing subject-oriented information. Currently available keywords access are merely retrieval systems of titles, and nothing further. Contents data should be added to the bibliographic data of NACSIS-CAT for each library in order to effectively access to subject data on OPACs. There are some advantages in adding contents, such as: they remain unchanged once published; they need no maintenance; they offer a broader scope of technical terms; they give no room for subjective elements of those who input the information. On the other hand, working closely with publishing houses to key data into computers will certainly become inevitable. Moreover, standardization of words needs to be resolved. In order to put the idea into actual use, estimating the cost for adding contents information and evaluating its effectiveness must be made as an initial step.